Antimicrobial activity and beta-lactamase stability of foramidocillin. - Mandell, W (1986)
Foramidocillin is a 6-alpha-formamido penicillin with a 6-beta-acylureido side chain. The majority of the Enterobacteriaceae were inhibited by less than or equal to 1 microgram of foramidocillin per ml, and Pseudomonas aeruginosa was inhibited by 4 micrograms/ml. Foramidocillin had activity comparable to those of ceftazidime, imipenem, and aztreonam against beta-lactamase-producing members of the Enterobacteriaceae and P. aeruginosa, and it inhibited organisms resistant to piperacillin. Foramidocillin did not inhibit gram-positive species or anaerobic gram-negative bacteria. Foramidocillin was not hydrolyzed by the common plasmid-mediated beta-lactamases TEM-1, TEM-2, OXA-2, PSE-4, and SHV-1, by the chromosomal beta-lactamases P99 of Enterobacter cloacae and K1 of Klebsiella oxytoca, or by the Sabath-Abraham enzyme of P. aeruginosa.